2011
DOI: 10.3109/00365513.2011.628688
|View full text |Cite
|
Sign up to set email alerts
|

The standardization of urine particle counting in medical laboratories – a Polish experience with the EQA programme

Abstract: The standardization of urine particle counting methods continues to be a significant problem in medical laboratories and requires further recovery activities which can be conducted using the EQA scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 16 publications
0
12
2
Order By: Relevance
“…They showed that only 13% of laboratories use automatic systems for sediment examination. Moreover, even though laboratories are asked to use standardized procedure for sediment examination, only 29% of the results could have been considered to be standardized (16% – manual methods, 13% – automated systems) ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…They showed that only 13% of laboratories use automatic systems for sediment examination. Moreover, even though laboratories are asked to use standardized procedure for sediment examination, only 29% of the results could have been considered to be standardized (16% – manual methods, 13% – automated systems) ( 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, cytology is often complemented by other tests in parallel. Counting urinary particles is another important part of a routine urinalysis, providing a non-invasive and inexpensive clinical significance 55 . Urine microscopic examination is to identify and quantify the insoluble substances present in the urine under the microscope.…”
Section: Current Technologies For Urine-based Biomarkersmentioning
confidence: 99%
“…Many laboratories still apply the non-standardised coverslip method with decanting supernatant after centrifugation and inserting the drop of sediment on the slide. Thus, the low precision and wide uncertainty of results obtained with the coverslip method is observed (2,10). Chamber use standardises the volume of sample analysed under the microscope and analysis of uncentrifuged urine enables to avoid errors related with the centrifugation step.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, different protocols for manual methods can be applied in laboratories, varying in type of analysed specimen (stained or unstained), type of microscope used (bright-field or contrast-phase), the manner of expression of the results (per high power field (HPF) or in a volume unit). If a centrifuged sample is analysed, laboratories can also apply a different force and time of centrifugation, as well as the manner (decanting, using a pipette) and degree of urine concentration (2,(10)(11)(12). Thus, despite the availability of recommendations/guidelines for urine particle analysis, the standardisation of urine particle analysis procedures is poor (2,(10)(11)(12)(13).…”
Section: Introductionmentioning
confidence: 99%